Effect of virulent anaerobes on the outcome of peritoneal dialysis associated peritonitis - Narain, Upma; Gupta, Arvind (International Journal of Advances in Medicine, 2017)
Background: Anaerobic bacteria do not account much of peritoneal dialysis (PD) associated peritonitis; hence most of the reports do not discuss this issue. In the present study we analyze PD patients who developed anaerobic peritonitis. Methods: In between January 2000 to August 2015, we tried to analyze PD patients who have developed only anaerobic peritonitis as a single pathogen, the virulence and impact of those virulent anaerobes on the outcome. Results: In our retrospective study we identified 42 episodes of anaerobic peritonitis which include 36 patients of single episodes and 6 patients of two episodes. The microscopic examination of dialysate pellet revealed 55.6% gram negative bacilli, 36.1% gram positive cocci and 8.3% gram positive bacilli. Culture examination revealed 47.3% Bacteroides species, 16.7% Fusobacterium species, 13.7% Lactobacillus acidophilus, 16.7% Peptostreptococcus anaerobies, 2.8% Peptococcus and 2.8% Propionibacterium acnes. On analyzing the outcome data through chi test, we inferred that Bacteroides fragilis (36.1%) was the major cause of death among gram negative anaerobes while among gram positive anaerobes peptostreptococci (16.7%) was the major cause of death in majority of patients. Statistically significant association was found between virulent anaerobes and their outcome. Conclusion: Our results revealed that among both in gram negative anaerobes bacteroides fragilis and in gram positive anaerobes peptostreptococci were the major cause of death in PD associated anaerobic peritonitis. Hence prompt identification of virulent anaerobes may alarm us for early and judicious management to reduce morbidity, mortality and technique failure in PD associated anaerobic peritonitis.